Modelling individual preferences for environmental policy drivers: Empirical evidence of Italian lifestyle changes using a latent class approach. Issue 65 (November 2016) - Valeri, Eva; Gatta, Valerio; Teobaldelli, Désirée; Polidori, Paolo; Barratt, Benjamin; Fuzzi, Sandro; Kazepov, Yuri; Sergi, Vittorio; Williams, Martin; Maione, Michela
Highlights: We investigate public preferences for air quality policy drivers in Italy. We find heterogeneity in the personal engagement for changes in the mobility and eating habits. We simulate the ex-ante impact of potential air quality policies. The reduction of premature deaths and measure cost are important air quality policy drivers. Abstract: Degraded air quality severely affects the health of citizens worldwide. The design of effective policies requires exploring public preferences for environmental and air quality policy instruments. Within the EC-FP7 SEFIRA project, using a choice experiment that stresses the trade-offs between attributes, this study investigates public preferences for environmental policy drivers in Italy. The main objective is to investigate the role played by selected policy drivers in determining policy preferences, complemented by elasticity and willingness to pay estimations. Preference heterogeneity and the role of socio-economic and attitudinal variables are explored with a latent class model over 2400 respondents sampled across Italy. The results allow identifying the different role played by the policy drivers across the classes. It emerged that most of the respondents (43%) are particularly sensitive to the cost components (cost sensitive respondents). The remaining respondents instead show an important sensitivity towards personal engagement in term of changes in the mobility and eating habits (lifestyle-change sensitive respondents). However, while 29% of them perceive these habits' changes as negatively impacting on the personal utility, the other 28% of respondents translate the potential changes in the habitual behaviour of driving and eating as environmental and health benefits. Based on the modelling results, potential policies are simulated reporting respondents' reaction to selected scenarios. It shows the crucial role played by reduction of premature deaths due to atmospheric pollution and measure cost.